Combined Application of Manure and Chemical Fertilizers Alters Soil Environmental Variables and Improves Soil Fungal Community Composition and Rice Grain Yield - Iqbal, Anas; Ali, Izhar; Yuan, Pengli; Khan, Rayyan; Liang, He; Wei, Shanqing; Jiang, Ligeng (Frontiers in Microbiology, 2022)
Soil microorganisms play vital roles in energy flow and soil nutrient cycling and, thus, are important for crop production. A detailed understanding of the complex responses of microbial communities to diverse organic manure and chemical fertilizers (CFs) is crucial for agroecosystem sustainability. However, little is known about the response of soil fungal communities and soil nutrients to manure and CFs, especially under double-rice cropping systems. In this study, we investigated the effects of combined manure and CFs application to various fertilization strategies: (such as no N fertilizer (Neg-CF); 100% chemical fertilizer (Pos-CF); 60% cattle manure (CM) + 40% CF (High-CM); 30% CM + 70% CF (Low-CM); 60% poultry manure (PM) + 40% CF (High-PM), and 30% PM + 70% CF (Low-PM) on soil fungal communities structure and diversity, soil environmental variables and rice yield. Results showed that synthetic fertilizer plus manure addition significantly increased the soil fertility and rice grain yield compared to sole CFs application. Moreover, the addition of manure significantly changed the soil fungal community structure and increased the relative abundance of fungi such as phyla Ascomycota, Basidiomycota, Mortierellomycota, and Rozellomycota. The relative abundances dramatically differed at each taxonomic level, especially between manured and non-manured regimes. Principle coordinates analysis (PCoA) exhibited greater impacts of manure amendments addition than CFs on fungal community distributions. Redundancy analysis showed that the dominant fungal phyla were positively correlated with soil pH, soil organic C (SOC), total N, microbial biomass C, and the fungal community structure strongly affected by SOC. We conducted a structural equation model to examine the relationship between microbial biomass, soil nutrients, and grain yield. This analysis supported the hypothesis that soil nutrient content and availability directly affect rice grain yield while soil bacteria indirectly affect grain yield through microbial biomass production and nutrient levels. Network analysis explored positive relationships between microorganisms and could increase their adaptability in relevant environments. Overall, the findings of this research suggest that the integrated application of CF and manure is a better approach for improving soil health and rice yield.